The Effect of Profitability, Solvency, Cash Flow on Stock Returns - Arintaka, Lano; Nugraheni, Novita (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
The government's policy to implement the downstreaming of energy and raw materials from mining is not merely a fabrication. The government is progressively and sustainably enforcing the policy to cease the export of mineral resources, including nickel, tin, alumina, and bauxite. In 2022, Indonesia's export value in the mining sector and other sectors amounted to US$ 64.919 billion, reflecting a 71.22 percent rise compared to 2021, demonstrating the effectiveness of the nickel ore export ban policy enacted in 2020. The recent downstreaming, particularly in mining and the establishment of processing facilities, has prompted increased investor interest. The shares of mining industry companies are expected to exhibit long-term financial improvement. This study employs a quantitative research design to ascertain the impact of profitability, solvency, and cash flow variables on the energy and basic materials sector within companies listed on the Indonesia Stock Exchange (IDX) during the periods of 2019 and 2022, specifically those included in the LQ45 index in 2023. The research findings indicate that cash flow and profitability impact stock returns, but solvency exerts little influence.